Exploring novelties in the causal relationship between economic complexity and natural resource rent: Empirical insights from Nigeria and South Africa - Clement Olalekan Olaniyi; Nicholas M. Odhiambo (Journal of Open Innovation: Technology, Market and Complexity)
This study advances global understanding by introducing asymmetric structure into the causality between economic complexity and natural resource wealth in resource-rich countries, using the case studies of Nigeria and South Africa covering 1970–2021. This approach reveals hidden causality in the nexus and gives more informed policy options that align with socioeconomic realities and real-world events. This study adopts the Hatemi-J asymmetric causal framework that integrates bootstrap simulations with leverage adjustments. The findings report neither symmetric nor asymmetric causality in Nigeria. Meanwhile, South Africa's case appears different. Symmetric causality does not exist, but there is bidirectional asymmetric causality in the positive shock components of economic complexity and natural resource rent. Stakeholders in Nigeria should evaluate why natural resource wealth does not cause an increase in economic complexity and make concerted efforts to enhance economic complexity to become a significant antidote to reducing resource dependency and providing pathways to evade the resource curse. South Africa should refocus its economic complexity to foster the development of non-resource-based sectors and exports to spur economic diversification, reduce resource dependency, and mitigate the resource curse. The country should also allocate a greater portion of its resource income to initiatives that enhance economic complexity. Unlike country-specific policy implications, this study establishes that governments, stakeholders, policymakers, and scholars must consider the practical implications of asymmetric structures when analysing the relationship between natural resource wealth and economic complexity. Relying on linear models oversimplifies the complex realities and socioeconomic conditions of the real world.